Manajemen Penduduk dan Ketenagakerjaan yang Efektif: Pengembangan Sistem Manajemen Penduduk dan Ketenagakerjaan yang Responsif terhadap Kebutuhan Tenaga Kerja dan Industri di Kabupaten Jombang Melalui Teori Transisi Demografi - Usriya Fara Nabila (Lembaga Institute Development of Social Economic Cociety, 2025)
This article discusses the importance of effective population and workforce management in facing the challenges of mismatch between workforce skills and industry needs, especially in Jombang Regency. Using the demographic transition theory, the article highlights the opportunities of the demographic bonus and the challenges of the aging population as important backgrounds in designing an adaptive workforce system. Through the analysis of population and workforce data for the past five years, it was found that although the proportion of the productive age population in Jombang is high, there is still a gap in the provision of a workforce that is in accordance with the dynamics of the industry. Therefore, this article recommends strengthening institutions, integrating educational curricula with industry needs, and cross-sector collaboration in developing a training and job placement system that is responsive to demographic and technological changes.